O protesto social contemporâneo: o engajamento político via redes sociais no Brasil a partir de 2013 - Machado, Janaína Marissol dos Santos (2016)
Brazilian society has witnessed the uprising of several protests, which tend to start at some place, for reasons peculiar to it, and spread to another one, a city, a state or a country, taking then new e greater dimensions. In spite of the peculiarities of each one, these protests present common features, like heterogeneity, self-management, horizontality, personification and the organization by means of the social networks, aspects that were also present in the Brazilian recent manifestations of June 2013 and in the manifestations that took place after that. Regarding the protests of June, they began with very specific agendas; however, during these protests, other demands were brought together to the problem of the raising of the bus tickets. Among these agendas, the moral inflexion characterized in the struggle against corruption was highlighted and predominated in the national political scene, galvanizing part of the population of the country to the point of provoking the impeachment of President Dilma Rousseff. According to the data collected in this work, new forms of social contestation and protestation through social networks (Facebook) emerged in this period, in a way to characterize a new repertoire of collective action. Besides moral subjects of conservative nature, the political manifestations through the social networks were marked by a highly dualistic and emotional performance in the enlisting of new adherents to the cause. As it was also found, in the interviews, a group of conspiratorial theories is adopted in order to justify political engagement in the internet. These conspiratorial theories, that had been restrict to a certain group of people before, found in the digital social networks a way of an easier propagation, being available to anyone and ready to enlist a legion of followers that, in the social networks, give them feedback based on a common sense opposed to progressionist social change.